2008
DOI: 10.1007/s12041-008-0012-8
|View full text |Cite
|
Sign up to set email alerts
|

The hsrω 05241 allele of the noncoding hsrω gene of Drosophila melanogaster is not responsible for male sterility as reported earlier

Abstract: The hsrω 05241 allele of the noncoding hsrω gene of Drosophila melanogaster is not responsible for male sterility as reported earlier

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…This line, like the parental one from which it was derived, was associated with male sterility in the homozygous state. As in case of the parental hsrω 05241 stock, 69 recessive male sterility in the derived EP93D line was also due to a second site mutation which was recombined out. Likewise, recessive embryonic lethality in the original EP3037 stock was also recombined out.…”
Section: Non-coding Hsrω Rna and Polyq Toxicity In Drosophilamentioning
confidence: 99%
“…This line, like the parental one from which it was derived, was associated with male sterility in the homozygous state. As in case of the parental hsrω 05241 stock, 69 recessive male sterility in the derived EP93D line was also due to a second site mutation which was recombined out. Likewise, recessive embryonic lethality in the original EP3037 stock was also recombined out.…”
Section: Non-coding Hsrω Rna and Polyq Toxicity In Drosophilamentioning
confidence: 99%
“…For example, Dic61B codes for an axonemal dynein intermediate chain exhibiting strong testis-biased expression (FlyBase); it is required for development and precise assembly of sperm axonemes and is essential for male fertility in D . melanogaster [87,88]. Given the rapid evolution of sperm length in D .…”
Section: Resultsmentioning
confidence: 99%
“…The recessive male sterile ms 21 mutation was maintained with the TM6B balancer [7], which established its linkage to chromosome 3 [6]. To map the cytological location of the ms 21 mutation, a series of overlapping, molecularly defined Drosdel and Exelixis deficiencies spanning the entire third chromosome were used.…”
Section: Resultsmentioning
confidence: 99%
“…However, further studies on the hsrω 05241 allele revealed that the recessive male sterility, initially ascribed to the mutation in hsrω gene, was actually due to a background second site mutation, which was named as ms 21 [6].…”
Section: Introductionmentioning
confidence: 99%